Sistem Pendukung Keputusan Dalam Menentukan Kualitas Jambu Biji Unggulan Menggunakan Metode Weighted Product - Ferry Susanto; Agus Salim; Ade Sherly Novita Sari; Mardinato Mardinato (Institut Bakti Nusantara, 2018)
Psidum guajava L or often we call guava is a plant originating from the central United States and spreads this plant extends to Southeast Asia, precisely Indonesia. Guava is one of the superior fruits that have a productive market. The support system is a system that is used to assist the process in determining the quality of superior guava products using the weighted product method which is one method used to find optimal alternatives from various alternatives. through the multiplication method to connect the rating attribute where each attribute must be raised using the specified attribute V1 = 0.132661 V2 = 0.105908 V3 = 0.117061 V4 = 0.078243 V5 = 0.109166 V6 = 0.070103 V7 = 0.104337 V8 = 0.073385 V9 = 0.072149 V10 = 0.136982 from the calculation of the most appropriate value is the value of V10 = 0.136982.